Implikasi Lahirnya Undang-Undang Nomor 13 Tahun 2012 tentang Keistimewaan Daerah Istimewa Yogyakarta terhadap Status Hukum Pakualaman Ground di Kabupaten Kulon Progo - Novi Achmadiah Rahmahsari (Lex Renaissance, 2017)
AbstractThis study intend to find out about how the application of UUK as seen from Implementation of UUK in registration rights of PAG's Land and next step about that in Kulon Progo regency. The results of this study is have been done a lot of improvement of policies related to privilege of DIY from colonial times until the enactment of UUK, That the registration and next step about registration rights of PAG's Land in Kulon Progo Regency still used the same procedure such as PP 24/1997. So it will be better to design a new system that is more efficient in handling PAG as soon as possible and provide education to people about the importance of having evidence right of land.Keywords: Pakualaman Ground, Land, Law - Law Feature DIY